Use of a non-medicated tape in non-specific low back pain: A single-blind, randomized, placebo-controlled trial - Lavagnolo, Umberto; Ricci, Matteo; Cason, Mattia; Vecchini, Eugenio; Maluta, Tommaso; Bertinato, Chiara; Sartori, Sabrina (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Low back pain (LBP) is prevalent and often non-specific disease. Kinesiology taping shows mixed evidence, and far-infrared (FIR)–reflecting tapes are promising. To evaluate the efficacy of an FIR-reflecting tape (FT) versus standard kinesiology tape (KT) and placebo for chronic non-specific LBP. Methods: A single-blind trias was conducted evaluating adults patients (aged 30–60 years) with chronic LBP >6 months, NRS 6–10, no radiculopathy or red flags; n=240 randomized (FT, n=80; KT, n=80; placebo, n=80). Tapes were applied to the lumbar region for two 5-day applications separated by a 3-day interval (total 14 days). Outcomes at T0, T1 (day 5), T2 (day 8), and T3 (day 14) included pain (NRS), disability (Roland-Morris Disability Questionnaire, RMDQ), and lumbar range of motion (ROM). Non-parametric analyses (Shapiro–Wilk; Kruskal–Wallis; Friedman) with α=0.05. Results: All participants completed the protocol with no adverse events. Groups were comparable at baseline. Between-group differences favored FT at all post-baseline time points for NRS, RMDQ, and ROM (p<0.05). FT reduced NRS from 8.09±0.89 to 2.19±0.92 at T3 (p<0.001), versus KT 8.15±0.84→4.00±1.21 (p<0.01) and placebo 7.95±0.83→6.54±1.40 (p<0.05). RMDQ improved to 12.13±2.72 with FT (p<0.001) vs 15.26±2.75 (KT, p<0.01) and 18.33±2.75 (placebo, ns). ROM gains were greatest with FT (p<0.001). Conclusions: FT tape produced superior pain relief, disability reduction, and mobility gains over 14 days compared with standard kinesiology and placebo tapes. FT tape offers a safe, drug-free adjunct to outpatient LBP care, potentially accelerating pain reduction and functional recovery.